POPULATION DYNAMICS OF PENAEID PRAWN PENAEUS MERGUIENSIS OFF MUMBAI COAST - BHADRA, SUMAN; BIRADAR, R. S. (Journal of Indian Fisheries Association, 2015)
Stock dynamics of Penaeus merguiensis was studied using length composition data collected seperately for males and females during the period 1995-1998, at New Ferry Warf landing, centre in Greater Mumbai. Food and feeding, sex ratio, facundity and length-weight relationships were worked out on a representative sub-sample. Asymptotic length (Loo) and growth coefficient (K) were estimated to be 220 mm and 1.80 per annum respectively for males. These parameters were respectively 281 mm and 1. 72 per annum in the case of fmnales. The instantaneous rate of total mortality coefficient (Z) was found to be 9.79 and 7.44 per annum for males and females respectively. The annual natural mortality coefficient (M) was estimated to be 2.80 for males and 2.60 for females. As the exploitation ratio exceeded 0.5 in the case of both the males and females, the study suggests the necessity for reduction in fishing pressure in order to achieve Maximum Sustainable Yield (MSY). Keywords - Banana Shrimp, mortality, Stock assessment, MSY.